Chaetomitrium Spinosum - Monica Suleiman; Hiroyuki Akiyama (2014)
(1) Plants are densely branched; (2) stem leaves are more or less rugose, and apices are strongly constricted or wavy; (3) leaf margins are incurved on one side, serrate on upper half with simple teeth, entire below, and denticulate near the apices; 4) costae are short; (5) lamina cells are laxly spinose-prorate above with simple spines on the back, smooth or distantly prorate below; (6) setae are 15 - 20 mm long, setulose almost to the base and papillose at extreme base; (7) calyptrae are cucullate, densely hispid all over and almost naked at the base.